(3GddHGH aj GdLeY Hjf GdSfI hGdcJGHs - (3Ydj Hf RcQjG Hf eSYhO GdMfaj,J (B686 (3g` s ((3GdeOQSI GdXGgQjI HGdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg Ydi BdGFg hfYeGFg hHYO aEfi deG QCjJ CfGSkG jCNPhf efG hjSdHhf Yde GdMOjK YfG hjLYdhf Pdc YjHkG s
(3BNQgG (B:s
(3hdG NdGa Cf ef eGJ HYO eG hQK ejQGKkG bHd GdbSeg Cf fUjHg dhQKJg hcPG dhGQJO dG jHWd ejQGKg GdPi GSJMbg hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HBNQ GdfSNI ebGHdI SfI (B809 (3hGdebGHd Ydi Hf CMeO Hf GdfMGSs
(3HgG fXGe GdJYbjHIs
(3eQJH Ydi CHhGH Gdabg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
Keywords: (3GdMOjK h GdeUWdMs